Integrated metabolomics and proteomics reveal biomarkers associated with hemodialysis in end-stage kidney disease - Lin, Weiwei; Mousavi, Fatemeh; Blum, Benjamin C.; Heckendorf, Christian F.; Moore, Jarrod; Lampl, Noah; McComb, Mark; Kotelnikov, Sergei; Yin, Wenqing; Rabhi, Nabil; Layne, Matthew D.; Kozakov, Dima; et al. (Frontiers in Pharmacology, 2023)
Background: We hypothesize that the poor survival outcomes of end-stage kidney disease (ESKD) patients undergoing hemodialysis are associated with a low filtering efficiency and selectivity. The current gold standard criteria using single or several markers show an inability to predict or disclose the treatment effect and disease progression accurately. Methods: We performed an integrated mass spectrometry-based metabolomic and proteomic workflow capable of detecting and quantifying circulating small molecules and proteins in the serum of ESKD patients. Markers linked to cardiovascular disease (CVD) were validated on human induced pluripotent stem cell (iPSC)-derived cardiomyocytes. Results: We identified dozens of elevated molecules in the serum of patients compared with healthy controls. Surprisingly, many metabolites, including lipids, remained at an elevated blood concentration despite dialysis. These molecules and their associated physical interaction networks are correlated with clinical complications in chronic kidney disease. This study confirmed two uremic toxins associated with CVD, a major risk for patients with ESKD. Conclusion: The retained molecules and metabolite–protein interaction network address a knowledge gap of candidate uremic toxins associated with clinical complications in patients undergoing dialysis, providing mechanistic insights and potential drug discovery strategies for ESKD.